2021
DOI: 10.1007/s00432-021-03603-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance of initial LI-RADS 2018 treatment response in predicting survival of patients with hepatocellular carcinoma following TACE: a retrospective, single-center cohort study

Abstract: Purpose Treatment response following transarterial chemoembolization (TACE) is frequently evaluated with Liver Imaging Reporting and Data System Treatment Response (LR-TR) algorithm, but its association with patients’ outcomes is not supported in the literature. The purpose of this study was to provide such data. Methods A retrospective analysis of 99 TACE patients with stage A/B hepatocellular carcinoma according to Barcelona-Clinic Liver Cancer staging s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Similarly, no association between number of procedures nor time to achieve LTC and OS was found in the present study. This is in line with our recent study in which an adjusted analysis showed no significant prognostic value of the initial LR-TR response despite improved OS in the nonviable subgroup in the unadjusted model [29].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, no association between number of procedures nor time to achieve LTC and OS was found in the present study. This is in line with our recent study in which an adjusted analysis showed no significant prognostic value of the initial LR-TR response despite improved OS in the nonviable subgroup in the unadjusted model [29].…”
Section: Discussionsupporting
confidence: 92%
“…This also highlights the need for discussion of patients with equivocal tumor responses in a multidisciplinary tumor board setting. Importantly, previous analysis showed no significant differences in overall survival between patients with an initial equivocal response and those with a viable response [ 25 ]. This correlates with the results of previous studies, in which most of the equivocal observations were incompletely necrotic at histopathologic examination [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%